Evaluation of chimeric antigen receptor of humanized rabbit‐derived T cell receptor‐like antibody. Issue 10 (31st July 2022) - Nakamura, Tomoko; Kobayashi, Eiji; Hamana, Hiroshi; Hayakawa, Yoshihiro; Muraguchi, Atsushi; Hayashi, Atsushi; Ozawa, Tatsuhiko; Kishi, Hiroyuki
Abstract: T‐cell receptor (TCR)‐like Abs that specifically recognize antigenic peptides presented on MHC molecules have been developed for next‐generation cancer immunotherapy. Recently, we reported a rapid and efficient method to generate TCR‐like Abs using a rabbit system. We humanized previously generated rabbit‐derived TCR‐like Abs reacting Epstein–Barr virus peptide (BRLF1p, TYPVLEEMF) in the context of HLA‐A24 molecules, produced chimeric antigen receptor (CAR)‐T cells, and evaluated their antitumor effects using in vitro and in vivo tumor models. Humanization of the rabbit‐derived TCR‐like Abs using the complementarity‐determining region grafting technology maintained their specificity and affinity. We prepared a second‐generation CAR using single‐chain variable fragment of the humanized TCR‐like Abs and then transduced them into human T cells. The CAR‐T cells specifically recognized BRLF1p/MHC molecules and lysed the target cells in an antigen‐specific manner in vitro. They also demonstrated antitumor activity in a mouse xenograft model. We report the generation of CAR‐T cells using humanized rabbit‐derived TCR‐like Abs. Together with our established and efficient generation procedure for TCR‐like Abs using rabbits, our platform for the clinical application of humanized rabbit‐derived TCR‐like Abs to CAR‐T cells will help improve next‐generation cancer immunotherapy. Abstract : The humanized TCR‐like antibody had a similar specificity and affinity for BRLF1/A24 as the original rabbit antibody. The TCR‐like CAR‐T cells generated from the humanized rabbit‐derived TCR‐like antibody demonstrated efficient cytotoxicity in vitro and in vivo.